"We are like the Poles": On the ambiguous labour market position of young Icelanders - Margrét Einarsdóttir 1963-; Jónína Einarsdóttir 1954-; Guðbjörg Linda Rafnsdóttir 1957- (2015)
Fræðigreinar Paid work is quite common amongst young people under the age of 18 in the Western world, although most undertake flexible part-time work. Nevertheless, studies on their labour market position are rare. The aim of this article is to examine the labour market position of young people in Iceland, a high-income Nordic country. We ask about: (i) young people’s general labour market rights regarding payslips and formal work contracts; (ii) their special labour market rights, safeguarded by child labour laws, in relation to rest periods, working hours, the prevalence of injuries and the consequent absence from work, and; (iii) the young persons’ own perceptions of their labour market position. The study is based on mixed methods: a survey (N = 952) and group interviews (N = 42) with 13-17-year-olds. The research reveals that the labour market position of young people is characterised by ambiguity. While their general rights to employment and decent pay are recognised to some extent, their work often violates child labour laws and accidents do occur. Young people commonly perceive their labour market position as weak. Their position in society, on the other hand, allows them to quit when confronted with an adverse work environment or if the work interferes with other duties. To conclude, education on occupational health and safety (OHS) and additional research on their labour market position are needed.